Design Of Vehicle Data Security System And Vehicle Number Certificate Of UNPAB Lecturers And Students Based On NFC - Muhammad Syam Pratama Batubara; Solly Aryza; Adi Tarigan (INFOKUM, 2021)
The rapid development of information and communication technology, including the development of detection and security technology, makes smartphone functionality more powerful, including not only as a communication tool but also as a source of information. In this study discussed the detection of lecturers and students' vehicles with NFC-based vehicle number letters where the rapid development of information and communication technology is directly related to the community's need for information that aims to facilitate the collection of increasingly sophisticated cars. This Android-based app can read information about the car, especially tags that contain vehicle certificates.